Multiple model adaptive control of neuromuscular blockade: Design guidelines and clinical cases - Teresa Mendonça (2007)
The high level of uncertainty of the dynamic response of patients subject to anaesthesia motivates the use of adaptive control methods. This paper proposes an approach based on Switched Multiple Model Adaptive Control (SMMAC) to tackle this problem in what concerns the control of the neuromuscular blockade level. It is shown how to design the different elements of the SMMAC controller, enhancing the importance of the observer polynomial, that is shown to be instrumental to stabilize the loop. Clinical results using atracurium as blocking agent are reported, thereby illustrating the application of the proposed approach in actual clinical practice.